Educational Patterns of Children Aged 7-15 Years in Fish Merchant Families (Case Study In Apitaik Village, Pringgabaya District, East Lombok) - Muasilaturahmi, Muasilaturahmi; Salman, Muhammad Ilyas; Suud, Suud (Journal of Social Science and Education Research, 2024)
This study aims to describe the educational patterns of children aged 7-15 years and the development of children's education based on the educational patterns applied by their parents. This research uses a qualitative approach of case study method. The subjects in this study were seven parents (mothers) and seven children aged 7-15 years. This research was conducted in Apitaik Village, Pringgabaya Sub-district, East Lombok Regency. Data collection techniques in this study used observation, interview and documentation techniques. Then the data was analyzed through the stages of data reduction, data presentation and conclusion drawing. The results of this study show that: (1) Subjects use three educational patterns, namely (a) permissive pattern, (b) authoritarian pattern, and (c) democratic pattern. Based on the results of the study, there were three subjects who used permissive parenting patterns, one subject used a combination of authoritarian and democratic patterns and three other subjects used democratic patterns.  The choice of parenting patterns is caused by factors of parental education, family economy, and parents' occupations. Children who receive permissive parenting are unable to socialize well and have a dominating nature that does not want to lose. While authoritarian patterns tend to be quiet just follow along, both are proven to have an unfavorable impact on children's social-emotional development.  In contrast to democratic parenting, which has a good impact on social emotional development, children become friends because they are good at placing themselves in the social environment. (2) The educational development of each child based on the educational patterns received from parents is different. Children who get permissive education patterns have mediocre educational development in contrast to children who get authoritarian and democratic education patterns who are far more accomplished.